Reptilia, Squamata, Dipsadidae, Xenodontinae, Taeniophallus brevirostris (Peters, 1863): Distribution extension and new state record - Morais, Drausio Honorio [UNESP]; Mott, Tami; Kawashita-Ribeiro, Ricardo Alexandre; Santos-Jr, Alfredo P. (Pensoft Publishers, 2010)
Taeniophallus brevirostris is a dipsadid snake widely distributed in Amazon. Here we report a new Brazilian state record for the species, improving our knowledge of its geographic distribution. On 15 May of 2008, one female specimen was collected at Serra do Santo Expedito, Aripuanã municipality, state of Mato Grosso, Brazil. This is the first record of this species for the state of Mato Grosso and extends its distribution ca. 300 kilometers from the nearest localities presented in literature. © 2010 Check List and Authors.